PENGARUH KEPADATAN HAMA KEPIK LABU (Leptoglossus australis F.) TERHADAP KERUSAKAN BUAH MENTIMUN (Cucumis sativus L.) - HANDAYANI, WURI; SARBINO, SARBINO; RAMADHAN, TRIS HARIS (Jurnal Sains Mahasiswa Pertanian, 2016)
ABSTRAK                  Leptoglossus australis F. is one of the pests of cucumber that reduce the quality and quantity of yield. This study was aimed to see how many L. australis can cause damage. The study was conducted in the village of Rasau Jaya 1, subdistrict. Rasau Jaya, district. Kubu Raya. The design used was a randomized block design (RAK) with the level of treatment were the number of  L. australis infested (control without bug, 1 bug, 2 bug, and 4 bug L. australis) with six repetitions. L. australis used for the test is the tree instars of  Leptoglossus at the age of infested fruit 4 days after anthesis. Cucumber damage is measured by the length of the fruit, fruit diameter and weight of cucumber. The results showed that one bug is already capable of inflicting damage and loss of cucumber fruit.